Acceptance and Commitment Therapy Boosts Subjective Well-Being of Emerging Adults but Leaves Emotion Regulation Unchanged - Yahya, Anna Nadia Febrina; Oriza, Imelda Ika Dian (Universitas Negeri Padang, 2024)
Emerging adulthood is a period of transition to early adulthood characterized by unstable conditions due to changes in many aspects of life. Psychological skills are needed that can help emerging adults face future challenges. This study aims to see the impact of Acceptance and Commitment Therapy in improving subjective well-being and emotion regulation in emerging adults. The participants of this study consisted of eight persons. The criteria for participants in this study are individuals aged 17-19 years who did not show indications of anxiety, depression and stress disorders. The selection of these non-clinical criteria is intended so that healthy individuals can achieve better psychological conditions and as a preventive effort to avoid psychological disorders. The measuring instruments used in this study are the Satisfaction with Life Scale (SWLS) and The Emotion Regulation Questionnaire (ERQ) Scale. The data analysis method used is paired sample t-test to measure the difference in the average score in the group before and after the intervention. The results of the analysis proved that there was a significant increase in subjective well-being scores between before and after the intervention by increasing the life satisfaction. On the other hand, there was no significant difference in emotion suppression scores, however there was a decrease in the use of expression suppression strategies in regulating emotions. The results also show there is a decrease in the use of cognitive reappraisal strategies in regulating emotions between before and after the intervention, but the decrease is not significant. This study provides implications for counseling practice with ACT based interventions to provide more skills in observing and defusion technique in regulating emotions so that ACT is expected to improve individuals’ emotion regulation abilities.